Existence and Uniqueness of Solutions to Time-Delays Stochastic Fractional Differential Equations with Non-Lipschitz Coefficients (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider the existence and uniqueness of solutions to time-varying delays stochastic fractional differential equations (SFDEs)with non-Lipschitz coefficients. By using fractional calculus and stochasticanalysis, we can obtain the existence result of solutions for stochastic fractional differential equations.
Keywords: Existence and uniqueness; Stochastic fractional differential equations; Time-varying delays; Non-Lipschitz coefficients.